The role of biotransformation and chemical structure of drugs in the diagnosis of drug allergies - T. N. Myasnikova; V. V. Smirnov (Фармакокинетика и Фармакодинамика, 2024)
Relevance. Despite the fact that the pharmacological effect of drugs is well known and studied, unfortunately, it is impossible to predict the development of drug allergies, since the individual characteristics of the body's reactivity are of great importance in its development. The goal is to analyze the clinical situation of the development of drug allergies to illustrate the importance of the role of biotransformation and the chemical structure of drugs in its diagnosis.Methods. The study was carried out on the patient after signing informed consent and included anamnesis, physical examination, skin prick tests with inhalant allergens, installation of a peripheral venous catheter, and provocative testing.Results. prick tests with: 0.9 % NaCl solution (negative control), histamine solution (10 mg/ml) (positive control), amoxicillin + clavulanic acid (100 mg + 20 mg), ampicillin (100 mg/ml), cephalexin (50 mg/ml) — positive results, ceftazidime (20 mg/ml), clarithromycin (20 mg/ml) — negative results; intravenous tests with: 0.9 % NaCl solution (negative control), ceftazidime (2 mg/ml), clarithromycin (0.01 mg/ml) — negative results; oral PDT with cefuroxime (cumulative dose — 250 mg), josamycin (cumulative dose — 1000 mg) — negative results. As a result of skin testing, LA for the amino group of beta-lactams was confirmed; No data have been obtained for LA on the beta-lactam ring, clavulanic acid, or macrolides.